CRITICAL THINKING IMPROVEMENT USING VIDEO CRITIC LEARNING STRATEGY BASED ON ATONG - Habib Nurrokhman (Universitas Negeri Islam Sumatera Utara, 2024)
This Classroom Action Research aims to improve the critical thinking of students on Theme 7 The Beauty of Diversity in My Country using video critic learning strategy based on ATONG in Grade IV SD Negeri 3 Karangtengah. This research was conducted in three cycles with one meeting each cycle. One cycle consists of four stages, namely planning, implementation, observation and reflection. Result of the research on Theme 7 The Beauty of Diversity in My Country using video critic learning strategy based on ATONG showed an increase in the critical thinking of students. The first cycle evaluation test obtained an average of 68 with 19 students above the minimal completeness criteria, the second cycle evaluation test obtained an average of 77 with 24 students above the minimal completeness criteria, and the third cycle evaluation test obtained an average of 79 with 24 students above the minimal completeness criteria. The number of students above the minimal completeness criteria has reached the specified success indicator.